Theoretical model for prediction of surface roughness in abrasive slurry jet polishing of glass. (6th May 2022) - Anbarasu, K.G.; Vijayaraghavan, L.; Arunachalam, N.
In the present work, the surface roughness generation of BK7 glass at low impact angle of jet with respect to process parameters has been predicted by using the depth of jet penetration model. Thus, first, depth of jet penetration model was developed by considering erosion theory, material removal characteristics (nozzle footprint) at the low angle of impact and process kinematics. The predicted depth of jet penetration was used to calculate the reduction in surface peaks and valleys height in order to predict the surface roughness. The predicted surface roughness is in close agreement with the experiment. Further, the developed depth of the jet penetration model was applied for the simulation of surface roughness with respect to process parameters and the most sensitive parameters were found by using sensitivity analysis.